Research and Test of X-wing Flapping-wing Mechanism Based on the Crank Slider Mechanism - Huang Xiansheng; Cai Yu; Li Qi; Liu Bin (Jixie chuandong)
A X-wing flapping-wing mechanism with wings flapping symmetrically is designed. The crank slider mechanism is adopted to convert the circular motion of the crank into the linear reciprocating motion of the straight shaft, and the straight shaft drives the wings on both sides through the rocker to realize the symmetric flapping of the wings. A prototype of the flapping-wing mechanism is made, and the motion test of the flapping-wing mechanism is carried out using an optical motion capture system and a wind tunnel. The reliability of the flapping-wing mechanism is analyzed from the flapping angle amplitude, the flapping frequency, the lift generated, and the operating condition of the motor. Through comparative experiments, a set of suitable flapping angle amplitudes and wing surface areas are determined, so that the flapping-wing mechanism could generate 12.9 g of lift, and it is verified that the clap-fling mechanism could effectively improve the lift of the flapping-wing mechanism.